Persistent voting decisions in shareholder meetings - Piñeiro-Chousa, Juan (2017)
This study examined the determinants of voting decisions in shareholder meetings, with a special focus on voting persistence. The data captured votes on managerial proposals in shareholder meetings held by U.S. banks between 2003 and 2013. The dynamic panel data were analyzed using robust two-step system generalized method of moments estimation (GMM) with orthogonal deviations. The lagged voting decision was a significant factor in explaining subsequent voting decisions. This finding provides evidence of voting persistence. Although persistence is a prominent topic in behavioral economics, studies have tended to focus on buying, consumption, and investment decisions. Persistence in voting decisions at the corporate level has been underexplored, so this article contributes to the behavioral economics literature.